The journey of gestational surrogacy: religion, spirituality and assisted reproductive technologies - Fisher, Ann M. (International journal of children's spirituality, 2013)
This article discusses the intersection of women’s experiences with the assisted reproductive technological practice of gestational surrogacy and spirituality and religion. During the interviews of eight gestational surrogates themes of spirituality-, religion- and faith-based language emerged as these women shared their narratives of assisted reproductive technologies in this Canadian study. Professionals supporting women before, during and after the experience of gestational surrogacy need to be mindful of the significance of spirituality and religion in third party reproduction practices for many women. In discussing these topics with gestational surrogates counsellors, child and youth care practitioners, faith leaders, social workers, and educators need to remain open and attentive to a multiplicity of diverse theological negotiations.